If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying 2t + -3 = -19 Reorder the terms: -3 + 2t = -19 Solving -3 + 2t = -19 Solving for variable 't'. Move all terms containing t to the left, all other terms to the right. Add '3' to each side of the equation. -3 + 3 + 2t = -19 + 3 Combine like terms: -3 + 3 = 0 0 + 2t = -19 + 3 2t = -19 + 3 Combine like terms: -19 + 3 = -16 2t = -16 Divide each side by '2'. t = -8 Simplifying t = -8
| y=-4-19 | | 4w+6=22w | | W+19=47 | | 2a=2.8 | | 4m-2n=18 | | 7+3k=-14 | | 145x=(106)(145)+106x | | y=-4(-5)-19 | | 155x=(106)(155)+106x | | -3(n-2)+5n=2(-3n+4)-2n+1 | | 7x-3+5x+3=180 | | 4(3x-5)+6=2x-14 | | 24=-4m | | 7x-3+5x+3=90 | | 2x-6=52 | | 13=(5-8m) | | -9(4x-6)=27 | | -4(4-3m)=-52 | | 16n^2-36= | | -17=5n-20 | | -(6x+(4x+3))=7-(5x+6) | | px-qr=-r | | 3(x-1)+8=-10 | | 2*3*4x-2*3*5x=6 | | 2=4c-2 | | 6n-20+5n=2(n+4)+4n-35 | | 6m=3m+36 | | 625=25g-105 | | -3=-2/3(x+2) | | (p^2-16)(p^2-3p-4)=0 | | 6m^2-18m-16= | | 9-4m=3 |